2006
DOI: 10.1177/1090198106288982
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Trials on Consider This, a Tailored, Internet-Delivered Smoking Prevention Program for Adolescents

Abstract: The Internet may be an effective medium for delivering smoking prevention to children. Consider This, an Internet-based program, was hypothesized to reduce expectations concerning smoking and smoking prevalence. Group-randomized pretest-posttest controlled trials were conducted in © 2008 by SOPHE Address correspondence to: David Buller, Klein Buendel, Inc., 1667 Cole Boulevard, Suite 225, Golden, CO 80401; dbuller@kleinbuendel.com. HHS Public Access Author Manuscript Author ManuscriptAuthor Manuscript Author … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
77
1
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(81 citation statements)
references
References 53 publications
(62 reference statements)
2
77
1
1
Order By: Relevance
“…In our zeal to be parsimonious and systematic in our review, we may have discarded other potentially valuable studies (e.g., Buller et al, 2008).…”
Section: Limitationsmentioning
confidence: 97%
“…In our zeal to be parsimonious and systematic in our review, we may have discarded other potentially valuable studies (e.g., Buller et al, 2008).…”
Section: Limitationsmentioning
confidence: 97%
“…As reported by Buller et al (2008), delays during this phase of the programme schedule may result in an extension between pretesting and implementation of a programme. This may cause loss of participants and valuable data.…”
Section: Resultsmentioning
confidence: 98%
“…This may cause loss of participants and valuable data. 36 In the case of IDEFICS, information on season-specific eating and activity behaviour of the children would have been lost. It is recommended to consider the possibility of delays as part of the development of instruments and procedures, and to foresee sufficient resources in the planning stage of a study.…”
Section: Resultsmentioning
confidence: 99%
“…5,25−27 In the present study, we were interested in whether a rich multimedia Web site containing content that provided training and resources, and facilitated communication, would improve how well local tobacco control coalitions functioned. A growing literature has confirmed that well-designed Web-based programs can be effective in improving the behavior of individual users to prevent or treat several chronic diseases (eg, asthma, 28 breast cancer, 29,30 healthy body image, 31,32 healthy eating behavior, 33−36 HIV, 37 panic disorder, 38 smoking uptake, 39 tinnitus, 40 and weight management 41−45 ). The Internet may be a promising channel for supporting community capacity building and action.…”
mentioning
confidence: 97%